2017
DOI: 10.1177/2050640616684404
|View full text |Cite
|
Sign up to set email alerts
|

Oesophageal candidiasis and squamous cell cancer in patients with gain‐of‐function STAT1 gene mutation

Abstract: CMC is not a well-recognised condition in gastroenterology practice and clinicians need to be aware of the genetics of the condition as well as the risk for oesophageal cancer so that they can counsel their patients and arrange surveillance appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
1
24
0
Order By: Relevance
“…Patients with CMC have an increased risk of both oral and oesophageal cancer (Koo, Kejariwal, Al‐Shehri, Dhar, & Lilic, ; Mohd Bakri, Mohd Hussaini, Rachel Holmes, David Cannon, & Mary, ), with patients often presenting at a much younger age than those without CMC. In the Toubiana paper, 6% of CMC patients developed cancer at a median age of 43, compared to an age‐adjusted expected rate of 1.1%, with the majority developing squamous cell carcinomas of skin, larynx and gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with CMC have an increased risk of both oral and oesophageal cancer (Koo, Kejariwal, Al‐Shehri, Dhar, & Lilic, ; Mohd Bakri, Mohd Hussaini, Rachel Holmes, David Cannon, & Mary, ), with patients often presenting at a much younger age than those without CMC. In the Toubiana paper, 6% of CMC patients developed cancer at a median age of 43, compared to an age‐adjusted expected rate of 1.1%, with the majority developing squamous cell carcinomas of skin, larynx and gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of muco-cutaneous candidiasis in these patients, a hallmark of the disease, was initially unknown and not attributed to autoimmune dysfunction [4]. More recent studies found that the disruption of the T helper-17 cell (Th-17)-based adaptive immunity to fungal infection is responsible for the chronic mucocutaneous candidiasis (CMC) [9]. Patients with APS type1 produce autoantibodies against specific Th-17 cells cytokines mainly IL17A, IL-17F, and IL-22 thus disrupting the innate antifungal immunity [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies found that the disruption of the T helper-17 cell (Th-17)-based adaptive immunity to fungal infection is responsible for the chronic mucocutaneous candidiasis (CMC) [9]. Patients with APS type1 produce autoantibodies against specific Th-17 cells cytokines mainly IL17A, IL-17F, and IL-22 thus disrupting the innate antifungal immunity [9,10]. Hypoparathyroidism is usually the first endocrine disorder to manifest during the course of the disease and has been reported in about 70-93% of cases.…”
Section: Discussionmentioning
confidence: 99%
“… 13 STAT1 GOF variants are also reported to be associated with various kinds of infectious disease, autoimmune disease, cerebral aneurysms, and cancer. 9 10 11 12 13 15 16 17 18 Regarding these topics, Toubiana, et al 9 recently reported detailed clinical spectrums in 274 patients from 40 countries with STAT1 1 GOF pathogenic variant: 98% of them had CMC, 37% had autoimmune manifestations, 21% had bronchiectasis, and 6% had mycobacterial infections, including tuberculosis and NTM infections.…”
Section: Discussionmentioning
confidence: 99%